Prevalence of Head Injury of Patients Arriving in a Tertiary Care Center - Yadav, Arbindra Kumar; Rajbanshi, Jagat Narayan; Kushwaha, Saroj Kumar; Nepal, Pankaj Raj (Eastern Green Neurosurgery, 2020)
Background and purpose: The prevalence of head injury is increasing with increasing number of automobiles, especially motorbike. With the objective to evaluate the prevalence of head injury and factors that could affect the severity of head injury, this study was performed in a tertiary hospital at far- eastern Nepal. Methodology: This is a cross-sectional study over the duration of one year. Association of age, gender, and mode of injury was checked with severity of injury using Chi-square test where P-value was kept significant at <0.01. Result: Total numbers of patient admitted through the emergency department, during the study period, were 832. Mean age of patient in the study group was 34.59 (SD 18.92) years. Majority of them falls in the category of 20-29 years. Among the different categories of head injuries, mild head injury (76%) was the most common presentation followed by moderate head injury and severe head injury, which were 14% and 10% respectively. Conclusion: Head injury seems to be the major cause of emergency admission in for eastern part of Nepal. Among them road traffic accidents seems to be the major burden which is more common in young gentlemen with significant number of severe head injury.